Bilateral versus unilateral orchidopexy: IVF/ICSI-ET outcomes - Fan, Lijuan; Shi, Lin; Liu, Shan; Zhang, Zhou; Shi, Juanzi (Frontiers in Endocrinology, 2024)
Introduction: Cryptorchidism is a common genital disorder. Approximately 20% of azoospermic or infertile men reported having histories of cryptorchidism. Bilateral cryptorchidism may have been more condemned than unilateral cryptorchidism. Early treatment by orchidopexy is the definitive procedure for cryptorchid patients with cryptorchidism. However, fertility potency after orchidopexy may be adversely affected and assisted reproduction techniques will be required for infertile patients. Objective: To compare the reproductive outcomes between unilateral and bilateral orchidopexy groups. Methods: A retrospective cohort study at a tertiary hospital, including a total of 99 infertile men who underwent orchidopexy to treat cryptorchidism and subsequently underwent their first IVF/ICSI-ET cycle. Men were grouped according to the laterality of their cryptorchidism and orchidopexy surgeries they received. Fertilization rate and live birth rate were chosen as parameters for evaluating outcomes. Results: The sperm concentration and viability were significantly higher in unilateral orchidopexy group than in bilateral orchidopexy group (28.09±27.99 vs 7.99±14.68, P=0.001; 33.34±22.52 vs 11.95±17.85, P=0.001). Unilateral orchidopexy group showed lower demand for ICSI (66.07% vs 95.35%, P<0.001). Interestingly, both groups exhibited similar rates of fertilization, clinical pregnancy, live birth and birth defect. Boy birth ratio was lower in bilateral orchidopexy group as compared to unilateral orchidopexy group (27.27% vs 58.62%, P=0.026). Conclusion: A history of bilateral orchidopexy surgery correlates with a worsened sperm parameter and a higher demand for ICSI as compared to patients with history of unilateral orchidopexy. However, this does not influence the final live birth rate.